CHARACTERISTICS OF CLINICAL AND LABORATORY MANIFESTATIONS DURING COVID - 19 WITH PNEUMONIA - Safoev Bakhodir Barnoevich; Turdiev Khurshid Kobilovich; Rakhimov Azizzhon Yakhyoevich (Scholar Express Journals, 2022)
The first outbreak of COVID-19 was recorded in December 2019, in Wuhan, China. Four months after the outbreak, who declared the COVID-19 pandemic (March 11, 2020), which indicates a high contagiousness of this infection. The entrance gate of the pathogen is the epithelium of the upper respiratory tract, epitheliocytes of the stomach and intestines. The initial stage of infection is the penetration of SARS-CoV-2 into target cells that have receptors for angiotensin-converting enzyme type II (ACE2 - angiotensin-converting enzyme 2). The new human coronavirus can cause a number of diseases - from mild forms of acute respiratory infection to severe acute respiratory syndrome (SARS). Extrapulmonary manifestations include: bleeding disorders, myocardial dysfunction and arrhythmia, acute coronary syndrome, acute renal failure, gastrointestinal disorders, hepatocellular lesions, hyperglycemia and ketosis, neurological diseases, eye symptoms and dermatological Complications
Keywords: COVID-19; SARS-CoV-2; covid-19; associated pneumonia